Konsep Kepemilikan Harta Dengan Maksimalisasi Laba Dalam Persfektif Islam - Anwar, Desy Rahmawati; M, Mahmud; Ista, Akram; Sutomo, Andi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article is related to the relationship between the concept of ownership and acquiring property by maximizing profits in an Islamic perspective, both of which are a unity related to economics where when talking about profits it will clearly be linked to profits and losses which in the concept are included in the economic realm but profits are in the discussion This is the acquisition of profits based on Islamic principles, and the concept of ownership in Islam is also related to economics where ownership is actually divided into 3, namely private, public and government ownership. If we talk about ownership, it is clear that one of the things we get from the efforts we make in economic terms is related to how we obtain property in a good way, for example doing business, trading, working in a company and there are many things we can do to obtain property. In this article, the concept of ownership will be related to profit or gain, how we carry out economic activities to make a profit in order to obtain property that is the property of an individual or group. The results of the discussion can be concluded that the concept of ownership obtained from maximization is permissible as long as it follows all the provisions of Islamic law while adhering to economic principles based on the Al-Quran and Hadith which are transparent, honest and fair.